2020
DOI: 10.1101/2020.02.28.970103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A common gene drive language eases regulatory process and eco-evolutionary extensions

Abstract: 3Synthetic gene drive technologies aim to spread transgenic constructs into wild 4 populations even when they impose organismal fitness disadvantages. The prop-5 erties of gene drive constructs are diverse and depend on their molecular con-6 struction, and differential selection pressure they impose in the varied ecological 7 situations they encounter. The extraordinary diversity of conceivable drive mech-8 anisms and the range of selective parameters they may encounter makes it very 9 difficult to convey thei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“… The above constraints on frequencies allow us to represent the dynamics of equation (2) on a de Finetti diagram. The frequency of the three genotypes (WW, WD and DD) without mate-choice ( h = 0) converge to Hardy Weinberg equilibrium (Gokhale et al, 2014; Verma et al, 2021). When we introduce the mate-choice parameter into the rate equations (1), the dynamics deviate from Hardy Weinberg equilibrium and is governed by the fixed points that appear in the interior of the de Finetti diagram.…”
Section: Model and Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“… The above constraints on frequencies allow us to represent the dynamics of equation (2) on a de Finetti diagram. The frequency of the three genotypes (WW, WD and DD) without mate-choice ( h = 0) converge to Hardy Weinberg equilibrium (Gokhale et al, 2014; Verma et al, 2021). When we introduce the mate-choice parameter into the rate equations (1), the dynamics deviate from Hardy Weinberg equilibrium and is governed by the fixed points that appear in the interior of the de Finetti diagram.…”
Section: Model and Resultsmentioning
confidence: 98%
“…Hence, an individual can be either of the three genotypes: WW, DD and WD. Previous work has shown that the gene drive can arise if a drive carrying genotype undergoes distortion, viability or fertility selection that acts during the different life stages of an organism (Verma et al, 2021). Hence, one can categorize various gene drive systems based on pre-existing standard population-genetic terminology (distortion, fertility selection and viability selection).…”
Section: Model and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the underlying population structure and selection pressures, two main modeling approaches have been developed: (i) discrete populations connected by migration, in which the gene drive allele frequency is tracked disregarding demographic changes, implying soft selection [6]; (ii) continuous space, where gene drive spread is modeled through spatial-demographic effects [5, 16, 19, 20]. These two approaches emphasize different aspects of selection affecting the gene drive allele frequency: in the initial stage of deployment, spread of the gene drive will depend mainly on direct competition between the gene drive and wild type alleles (i.e., soft selection) whereas at high frequencies the reduced fitness is expected to reduce the size of the population (i.e., hard selection).…”
Section: Introductionmentioning
confidence: 99%